Pengembangan Game Edukasi Mobile Augmented Reality untuk Membantu Pembelajaran Anak dalam Membaca, Menulis, dan Berhitung - Billawal Nadipa Pelealu; Tri Afirianto; Wibisono Sukmo Wardhono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Kids in their early age(born - 6 years) are experiencing rapid growth phase and they can learn all kind of knowledge, therefore they need a good guidance for their education. Beside books medium that can be used for education are video games. By playing video games childrens can have a fun and educational medium. Therefore this research develop a video game that can be played by childrens. Augmented reality used in the game in hopes that the game will looks attractive and makes the childrens be keen on learning. The game designed using iterative rapid paper prototype method because the more the game prototype iterate the better it will be. To test if the game is fun and makes children to have an interest in learning reading, writing, and calculating we test it with Fun Testing test and the result of that shown that the childrens are interested in learning reading, writing, and calculating. Childrens concept of reading, writing, and calculating are increasing shown by the mean score of the pre-test and post-test with the score of pre-test is 76 and the post-test is 80.